Impact of central nervous system‐directed treatment on competence and adjustment among children in early cancer survivorship. Issue 9 (10th July 2021) - Winning, Adrien M.; Moscato, Emily L.; Lehmann, Vicky; Keim, Madelaine C.; Rausch, Joseph R.; Lipak, Keagan G.; Himelhoch, Alexandra C.; Murphy, Lexa K.; Prussien, Kemar V.; Olshefski, Randal S.; Vannatta, Kathryn; Compas, Bruce E.; et al.
Abstract: Background: Central nervous system (CNS)‐directed treatments can cause long‐term academic, social, and emotional difficulties for children with cancer. However, limited research has examined the emergence of problems longitudinally and has often stratified risk by diagnosis alone. Therefore, this study compared competence and adjustment in children, who did and did not receive CNS‐directed treatment, over the first 3 years following a cancer diagnosis. Procedure: Mothers, fathers, and children (ages 5–18 years at diagnosis) from 217 families reported on the child's competence (academic, social) and adjustment (anxious/depressed, withdrawn/depressed) near a new cancer diagnosis or relapse and 3 years later. Children were categorized into CNS‐directed treatment ( n  = 112; including cranial radiation, intrathecal chemotherapy, and/or neurosurgery) and non‐CNS‐directed treatment ( n  = 105) groups. Results: At enrollment, there were few differences in competence and emotional adjustment among children based on treatment or diagnostic group. At 3 years, mothers and fathers reported poorer social competence for the CNS‐directed treatment group, and fathers reported poorer school competence for the CNS‐directed treatment group. Over time, father ratings of social competence increased for the non‐CNS‐directed treatment group, but not the CNS‐directed treatment group. While father ratings of academic competence declined for the CNS‐directed treatment group, mother ratings declined the most for children diagnosed with a brain tumor. All children demonstrated higher anxious/depressed scores over time. Conclusions: CNS‐directed treatment may be a valuable indicator to identify childhood cancer survivors at risk for poor competence during early survivorship. Follow‐up screening and supportive services are recommended, as well as additional longitudinal research.